A Comparison of Restricted Stock Grants Between Dual‐Class and Single‐Class Companies. Issue 3 (10th September 2018) - Li, Ji; Wu, Di; Zhou, Dan
Abstract : In recent years, quite a few new economy‐type companies have chosen a dual‐class stock structure. However, industry, investors, and academia have never reached consensus regarding such a structure. Under this context, this article investigates how dual‐class and single‐class firms apply performance‐based and time‐based restricted stock in compensating their executives to shed light on the debate. Results suggest dual‐class and single‐class firms pay similar amounts of stocks to their CEOs. Cash bonus payment accounts for larger percentage within total compensation and stock compensation accounts for a smaller percentage in dual‐class firms relative to single‐class firms. Dual‐class companies are less likely to use performance‐based and time‐based stock awards. Additionally, dual‐class firms vest their performance‐based stock grants over shorter periods compared with single‐class firms, but both types of firms vest their time‐based stock grants over similar periods. CEOs in dual‐class firms do not always receive stock compensation awards as quickly as those in single‐class firms. For performance‐based stock grants, a ratable vesting method is less common, but the cliff vesting method is more common in dual‐class firms. Such vesting arrangements of stock awards in the compensation plan motivate CEOs in dual‐class firms to target and meet long‐term growth goals and protect shareholders' interests.